Strategies for 'bloodless' surgery: the experience of cytoreductive surgery for peritoneal carcinomatosis in Jehovah's Witnesses. Issue 10 (28th June 2020) - Tse, Andrew; Chow, Oliver; Matar, Amer; Alzahrani, Nayef; Morris, David
Abstract: Background: Cytoreductive surgery (CRS) for the management of peritoneal carcinomatosis (PC) can involve significant blood loss which necessitates the transfusion of blood products. This poses a particular challenge in the Jehovah's Witnesses population whose beliefs do not permit the transfusion of blood products or blood‐related derivatives. This report describes the experience of one institution performing CRS with hyperthermic intraperitoneal chemotherapy (HIPEC) for PC in Jehovah's Witnesses and perioperative management strategies employed to avoid blood transfusion. Methods: A review of literature and prospectively collated data of Jehovah's Witnesses patients who underwent extensive CRS for PC and HIPEC for PC. Results: Four patients had CRS and HIPEC for PC. The median PC index score was 11 and complete cytoreduction was achieved in all cases. Primary tumours were ovarian ( n = 1), colorectal ( n = 2) and neuroendocrine tumour of gastrointestinal origin ( n = 1). The median difference between preoperative and postoperative haemoglobin was 38 g/L (23–43 g/L). Strategies included acute normovolumaeic haemodilution and autotransfusion within a closed circuit, autotransfusion from cell salvage and provisions for possible use of a haemoglobin based oxygen carrier. Ancillary measures identified and implemented to minimize transfusion dependence included, but were not limited to, preoperative iron infusion, perioperative acute haemodilution and cell salvage, administration of tranexamic acid, prothrombinex and use of paediatric tubes for venepuncture. Conclusion: The review suggests CRS and HIPEC for extensive PC can be done safely in circumstances where transfusion of allogenic blood products is not permitted.